STRATEGI NATION BRANDING KOLOMBIA MELALUI KAMPANYE “LA RESPUESTA ES COLOMBIA” - Iqbal Valensyah Purwanto; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The following study describes Colombia's nation branding practice that was implemented during Juan Manuel Santos' administration in 2010-2018. Colombia itself is a country located in South America that is often associated with a rather negative image and perception due to three critical issues that happened within the country: drug trafficking, insecurity and corruption. In order to create a positive image of its country, Colombia later implemented its own nation branding strategy through the "La Respuesta es Colombia" campaign. Researcher used constructivism as a perspective and the theory of nation branding strategy that was proposed by Keith Dinnie in this following study. The theory itself explains the strategies that are commonly used by a country in their nation branding campaign. Data were gathered using a qualitative research approach and document analysis method. Through those approaches, researcher gathered data that were found in books, academic publications, public documents and digital archives related to the issues that are being researched. This study shows that Colombia practiced its nation branding by releasing an advertisement that was aired in a few foreign television stations, digital and social media usage, appointing nation brand ambassadors and weaving a cooperation between stakeholders and local businesses. This nation branding campaign helps promote Colombia internationally through creating a positive, comprehensive and competitive image of the country in issues like cultures, environments, exports, tourism and investments. Keywords: Nation Branding, Nation Branding Strategy, Image, Perception, Colombia, La Respuesta es Colombia.